Moringa oleifera (Shajna): the wonderful indigenous medicinal plant - Taher, Mohammad Abu; Nyeem, Mohammad Abu Bin; Ahammed, Md Monir; Hossain, Md Mobarak; Islam, Mohammad Nazrul (Asian Journal of Medical and Biological Research, 2017)
The Tree of Life' or 'Miracle Tree' is the name of the plant of Moringa oleifera (Shajna). Moringa oleifera is one of the important plants in plant kingdom. Its leaves and fruits are used as vegetable in Indian sub continent, at the same time each part of the plant rich with some important medicinal values. It is now considered as a valuable source of several unique products for the medicines against various diseases. The present review is to focus on the nutritive values, physico-chemical properties, phyto-chemicals and pharmacological activities of M. oleifera. Various parts of the plant like seeds, leaves, flowers, bark and fruits have been investigated for their significant pharmacological activity. Phyto-chemicals like flavanoid, anthraquinone, alkaloids, essential oils, tannic acid, carotene, glucose have been reported for significant antioxidant, hepatoprotective, anticancer, aphrodisiac, antiinflammatory, antihyperlipidaemic, antihyperglycaemic and antiulcer activities of Drumstick tree and emphasizes the need for further exploring available information. Asian J. Med. Biol. Res. March 2017, 3(1): 20-30